Newer antithrombotic drugs - Sikka, Pranav (Medknow Publications, 2010)
Thromboembolic disorders are one of the disorders for which we are still on the look out for a safe and efficient drug. Despite the widespread use of antithrombotic drugs for the prevention and treatment of arterial and venous thrombosis, thromboembolic diseases continue to be a major cause of death and disability worldwide. This shows our inefficiency in searching efficacious and safe antithrombotic drugs. We have reached the basic mechanism of thrombus formation and by interrupting various steps of this mechanism, we can prevent as well as treat thromboembolic disorders. In continuation of Aspirin, now, we are using Clopidogrel, Ticlopidine and GpIIb/IIIa inhibitors (Abciximab, Tirofiban and Eptifibatide). Warfarin is an old antithrombotic drug which is still being used; but due to various side effects and drug interactions, we are bound to use newer drugs. Newer antiplatelet drugs include Prasugrel, Ticagrelor and Cangrelor, whereas newer thrombin inhibitors are Ximelgatran and Dabigatran. Apixaban is also a newer entry in this category as factor Xa inhibitor. Idrabiotaparinux is an indirect inhibitor of Xa as it accelerates the activity of antithrombin. Moreover, researches and trials for better and safe drugs are ongoing.